2022
DOI: 10.1155/2022/7640560
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Fetoprotein Ratio Predicts Alpha-Fetoprotein Positive Hepatocellular Cancer Patient Prognosis after Hepatectomy

Abstract: Background. This study was conducted to investigate the effect of alpha-fetoprotein (AFP) ratio on the prognosis of AFP-positive hepatocellular carcinoma (HCC) patients after hepatectomy. Methods. We retrospectively included 879 HCC patients with AFP-positive who underwent hepatectomy from February 2012 to October 2017 and randomly divided into training cohort and validation cohort. AFP ratio was equal to the AFP level within one week before hepatectomy to AFP level within 20-40 days after surgery. The end poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…13 In a previous study, we found that AFP-positive HCC patients with a low AFP ratio had a poorer prognosis compared to those with a high AFP ratio. 8 However, the prognostic significance of the AFP ratio in AFP-negative HCC patients after surgery remains unclear. Therefore, in this retrospective analysis, we aimed to investigate the impact of the AFP ratio in AFP-negative HCC patients after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 In a previous study, we found that AFP-positive HCC patients with a low AFP ratio had a poorer prognosis compared to those with a high AFP ratio. 8 However, the prognostic significance of the AFP ratio in AFP-negative HCC patients after surgery remains unclear. Therefore, in this retrospective analysis, we aimed to investigate the impact of the AFP ratio in AFP-negative HCC patients after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the AFP ratio was calculated as the ratio of serum AFP level within 1 week prior to surgery to serum AFP level 20-40 days after hepatectomy. 8 Follow-up data were collected from the patients' medical records.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation